Physical study of the response of tidal flat development to the reduction in the input of Yellow River sediment into the sea - Feng Yi; Feng Yi; Chao Zhan; Qing Wang; Xueyan Li; Kezhao Fang (Frontiers in Marine Science)
IntroductionOver the past three decades, approximately 16% of the world’s tidal flats have been lost. In the Yellow River Delta (YRD), the reduction in sediment supply due to decreased Yellow River discharge has raised concerns regarding the morphological stability of tidal flats.MethodsTo investigate the response of tidal flat development to reduced sediment input, a novel physical model experiment was conducted using natural silt from the YRD tidal flat. Offshore sediment concentration was decreased to simulate reduced sediment supply. An Argus system was deployed in the wave basin for the first time to capture the morphological changes during the experiment.ResultsThe results indicate that 94% of suspended sediment settles during its transport from offshore to the tidal flat. Suspended sediment concentration (SSC) in the subtidal zone increased during flood tides and decreased during ebb tides. With decreasing SSC, comb-shaped flow marks formed along the vertical shoreline in the intertidal zone, while the subtidal zone was dominated by the development of sand waves. For a given SSC, sand wave morphology and development patterns varied across different cross-shore profiles; conversely, for a given profile, different SSC levels led to distinct sand wave characteristics.DiscussionThis study demonstrates the significant influence of SSC on tidal flat morphology and sediment dynamics. The findings suggest that continued reductions in sediment supply could exacerbate erosion risks in the YRD, highlighting the need for sediment management strategies to preserve tidal flat stability.